Suffering in Romans - Wu, Siu Fung; Still, Todd D. 1966-; University of Divinity (Eugene, Oregon Pickwick Publications, 2015)
Most of the Jesus-followers in Rome would have been familiar with socioeconomic hardship. Suffering was a daily reality either for themselves or for someone they knew. Many lived below or just above subsistence level. Some were slaves, homeless, or chronically sick. Followers of Christ might have experienced persecution because of their refusal to take part in the local religious festivals. Suffering is, of course, a significant theme in Rom 5:1-11 and 8:17, 18-39. Paul mentions various types of affliction many times in these texts. How might Paul's audience have understood them? In Suffering in Romans Siu Fung Wu argues that Paul speaks of the vocation of the Jesus-followers to participate in Christ's suffering, with the purpose that they may be glorified with him. Indeed, their identification with Christ's suffering is an integral part of God's project of transforming humanity and renewing creation. It is in their faithful suffering that Christ-followers participate in God's triumph over evil. This is counter-intuitive, because most people think that victory is won by power and strength. Yet the children of God partake in his cosmic victory by their suffering, aided by the Spirit and the hope of glory
Revision of the author's thesis (Ph. D.)--MCD University of Divinity, 2014 under title: Suffering in Romans : an audience focused reading. - Includes bibliographical references (pages 249-261) and indexes
Keywords: Bible -- Criticism, interpretation, etc -- Bible; Suffering -- Biblical teaching; Hochschulschrift